Pengaruh Tiktok Shop terhadap Perilaku Konsumtif Pada Mahasiswa Pendidikan Ekonomi Stambuk 2025 - Dayana Rebecca Tampubolon; Mawar Rona Omastauli Gultom; Chalfyn Syalom A Veliften Hutabarat; Mona Sofia Yanti Naibaho; Pittauli Ambarita; Rivani Marselinna Gea (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2026)
This study aims to analyze the influence of TikTok social media platform usage on the consumer behavior of students in the Economics Education Study Program, Stambuk 2025, HKBP Nommensen University, Medan. The rapid development of TikTok as a social commerce platform has driven significant changes in the consumption patterns of the younger generation, particularly through viral content, live shopping features, and the influence of influencers and content creators. This study used a qualitative method with a literature study approach and an online questionnaire survey based on Google Forms with a four-point Likert scale to 16 student respondents. The research instrument covered three main dimensions, namely: (1) intensity of TikTok Shop use, (2) the influence of TikTok Shop content on consumer behavior, and (3) self-control ability based on economic literacy. The results showed that 87.5% of students use TikTok every day, 75% admitted to being interested in purchasing products featured in TikTok content, and 68.8% trusted product recommendations from influencers. However, it was found that an economics educational background played an important role as a moderator of consumer behavior, as indicated by 93.8% of respondents who tried to shop wisely and 75.1% who felt that economics helped control impulsive shopping urges. This study concludes that TikTok Shop significantly influences students' purchasing intentions, but this influence can be effectively moderated through adequate economic literacy and financial awareness.